MINORITAS MUSLIM DI AUSTRALIA DAN INGGRIS - Kartini, Indriana (Jurnal Penelitian Politik, 2016)
The war against terrorism has become the main topic and spread all over the world since the bombing of WTC building in September 11"' 2001. The issue is that rather fighting terrorist as the actor of terrorism, the war is blured with fighting Moslem people as the most victimized as the actor of terrorism. Moslems in Australia and United Kingdom, two countries that become close supporter o f USA in the war against terrorism, has suffered of negative public perception. It is interesting to analyse policy in those two US ’ close allies. The research that has been conduct compares policy of Australia and Britain after the bombing. Image of Moslem community in those countries is shaped by the role of mass media as the source of opinion. The war against terrorism has negative effect that it is victimizing Moslem community as the source of terror.